The relevance of redundancy in multimodal documents - Lautenbacher, Olli Philippe (Linguistica Antverpiensia, New Series – Themes in Translation Studies, 2019)
The aim of this article is to refine the role of redundancy in deferred multimodal communication, from the standpoint of both communicators and their audiences and, by extension, translators. What is advocated here is the idea of a recursive reading process consisting of three phases (perception, construction and integration) and that this process is based on the detection of a salient series of trigger stimuli that the communicator offers as incentives. The shared ground of significance of these trigger compounds actually reveals core meanings in the document, especially when there is exophoric reference. In the translation process, any change within this redundancy system, such as a modification in the balance between endophora and exophora, might alter the overall reception experience.